2000
DOI: 10.1023/a:1005441400107
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We determined the prevalence of celiac disease in subjects with autoimmune thyroiditis compared with sick and healthy subjects. The screening was performed with IgA-class endomysium antibody, by indirect immunofluorescence using human umbilical cord as the antigenic substrate. Six of the 172 patients with autoimmune thyroiditis were found to be anti-endomysium positive (3.4%) and five of these underwent intestinal biopsy, which showed total villous atrophy. By contrast, 3 (0.75%) of 396 patients with nongastro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(11 citation statements)
references
References 24 publications
2
7
1
1
Order By: Relevance
“…None of the other 5 coeliacs identified in our antibody screening had typical or atypical symptoms of coeliac disease. Unlike the previous report [11], we did not find other associated autoimmune diseases in our 7 patients with Hashimoto’s thyroiditis and coeliac disease. It must be, however, underlined that 2 of them, being still fairly young (aged 30 years or less), are likely to develop such a complication later on, and 2 of them, being males, are at a lower risk of multiple autoimmune syndrome.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…None of the other 5 coeliacs identified in our antibody screening had typical or atypical symptoms of coeliac disease. Unlike the previous report [11], we did not find other associated autoimmune diseases in our 7 patients with Hashimoto’s thyroiditis and coeliac disease. It must be, however, underlined that 2 of them, being still fairly young (aged 30 years or less), are likely to develop such a complication later on, and 2 of them, being males, are at a lower risk of multiple autoimmune syndrome.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study confirms the high prevalence of coeliac disease among patients with autoimmune thyroiditis with a slightly lower frequency (3.2%) than that reported in four previous studies including patients with both autoimmune thyroiditis and Graves’ disease (mean value 3.9%) [9, 10, 11, 12]. For the first time, IgA anti-tTG antibodies have been assessed in a large series of patients with autoimmune thyroiditis, giving better results than IgA EmA, which has been considered the best standardised test for coeliac disease screening up to now.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Previous studies reported that the frequency of CD in adults with AT varies from 3.2% to 3.4% [10][11][12][13]. Guliter et al [14] reported the prevalence of CD in adult Turkish patients with AT to be 5.9%.…”
Section: Discussionmentioning
confidence: 99%